2016
DOI: 10.1073/pnas.1604269113
|View full text |Cite
|
Sign up to set email alerts
|

Low-cost functional plasticity of TRPV1 supports heat tolerance in squirrels and camels

Abstract: The ability to sense heat is crucial for survival. Increased heat tolerance may prove beneficial by conferring the ability to inhabit otherwise prohibitive ecological niches. This phenomenon is widespread and is found in both large and small animals. For example, ground squirrels and camels can tolerate temperatures more than 40°C better than many other mammalian species, yet a molecular mechanism subserving this ability is unclear. Transient receptor potential vanilloid 1 (TRPV1) is a polymodal ion channel in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
76
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(76 citation statements)
references
References 50 publications
0
76
0
Order By: Relevance
“…We characterized temperature sensitivity of active ground squirrels and hamsters (Figure 1A) using a two-plate temperature preference test (Laursen et al 2016). We quantified the time spent by the animals on a reference plate set at 30°C or a test plate set to a temperature range from 0°C to 30°C.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We characterized temperature sensitivity of active ground squirrels and hamsters (Figure 1A) using a two-plate temperature preference test (Laursen et al 2016). We quantified the time spent by the animals on a reference plate set at 30°C or a test plate set to a temperature range from 0°C to 30°C.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, we reported that ground squirrels are tolerant to noxious heat, partially due to diminished heat sensitivity of the TRPV1 channel in peripheral nociceptors (Laursen et al 2016). Similar to TRPM8, the suppression of temperature sensitivity in squirrel TRPV1 is specific, as the channel remains sensitive to chemical agonists, such as protons and capsaicin, preserving its role in inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…These processes are energetically expensive, underscoring the notion that torpor is an active physiological process that requires molecular fine-tuning. Indeed, recent studies in hibernating rodents revealed profound genomically encoded changes in temperature sensors, mitochondrial function, protein control machineries, and cytoskeletal integrity [5, 6, 33]. We suggest the existence of other such modifications in various groups of enzymes, ion channels, and transporters implicated in energy homeostasis and ionic balance regulation.…”
Section: Discussionmentioning
confidence: 78%
“…For example, Voets et al suggested that temperature sensitivity arises from the activation energy associated with voltage-dependent gating 20 . Chimeric and ortholog analyses support a role of the linker region (connecting the N terminus to the pore domain) and the N-terminal domain in thermosensitivity 21,22 . On the other hand, involvement of the outer pore domain in heat sensitivity is supported by mutagenesis and modification of an external cation binding site 23,24 .…”
mentioning
confidence: 89%